Modeling Financial Performance District/City in East Java - Erna Hayati; Diah Ayu Novitasari; Shania Dwi Krispriandini (Jurnal Ekonomi Pembangunan, 2020)
This study aims to determine the relationship between Local Own-Source Revenue, Capital Expenditure, and Leverage on District/City Government's Financial Performance in East Java Province. The data used is the District/City Government's financial report data in East Java Province 2014-2018. The method used is panel data regression with the parameter estimation method, namely Generalized Least Square (GLS). The results obtained are the appropriate estimation model is the REM model. The variables that significantly affect districts/cities' financial performance in East Java are Capital Expenditure and Leverage, while Local Own-Source Revenue does not have a significant effect